2003
DOI: 10.1046/j.1365-2486.2003.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock changes and carbon sequestration potential of Flemish cropland soils

Abstract: Evaluations of soil organic carbon (SOC) stocks are often based on assigning a carbon density to each one of a number of ecosystems or soil classes considered, using data from soil profiles within these categories. A better approach, in which the use of classification methods by which extrapolation of SOC data to larger areas is avoided, can only be used if enough data are available at a sufficiently small scale. Over 190 000 SOC measurements (0–24 cm) have been made in the Flemish cropland (the Northern part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
71
8
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 19 publications
10
71
8
1
Order By: Relevance
“…Some recent studies suggest that SOC in European agricultural land is decreasing (Vleeshouwers and Verhagen, 2002;Sleutel et al, 2003). Bellamy et al (2005) used data from the National Soil Inventory of England andWales obtained between 1978 and to show that an average of 0.6% of the organic carbon content was lost per year from soils across England and Wales over that period, with some soils loosing up to 2 g kg -1 yr -1 (Fig.…”
Section: © Arwyn Jonesmentioning
confidence: 99%
“…Some recent studies suggest that SOC in European agricultural land is decreasing (Vleeshouwers and Verhagen, 2002;Sleutel et al, 2003). Bellamy et al (2005) used data from the National Soil Inventory of England andWales obtained between 1978 and to show that an average of 0.6% of the organic carbon content was lost per year from soils across England and Wales over that period, with some soils loosing up to 2 g kg -1 yr -1 (Fig.…”
Section: © Arwyn Jonesmentioning
confidence: 99%
“…the oldest and youngest possible ages to illustrate this. The SOC content of eroding soils (and hence also that of the deposited sediment) is expected to vary temporally: for example, previous studies have found that the C storage in the cropland of Flanders or Belgium has experienced a decrease of 5-18 % in the past decades (Lettens et al, 2005;Sleutel et al, 2003;Goidts and van Wesemael, 2007). Although it is not possible to reconstruct temporal changes in SOC content of surface soils for the last millennia, we assumed that a variation of 25 % with respect to the current values is a realistic range.…”
Section: Burial Efficiencymentioning
confidence: 99%
“…Such "change maps" express the data not in terms of simple concentrations but in terms of change in concentrations from 1992 to 2003. While GIS-based change maps have been produced for soil properties such as total carbon (Van Meirvenne, Pannier, Hofman, & Louwagie, 1996;Sleutel et al, 2003;Zhang & McGrath, 2004), to our knowledge, this is the first time change maps have been produced for TP in a wetland ecosystem. Mapping space-time trajectories of soil properties has applicability not only for Everglades wetlands, but also for various other types of ecosystems.…”
mentioning
confidence: 99%